Developing a project-based learning-based e-module to enhance critical thinking skills on vocational students - Rizal, Rifmelda; Ganefri, Ganefri; Ambiyar, Ambiyar (Universitas Negeri Padang, 2024)
This study aims to develop a digital simulation and communication e-module based on Project Based Learning by using Moodle application to improve critical thinking skills in the field of computer and network engineering. The main focus of this study is to assess the validity, practicality, and student responses to the developed e-module design. The study employed a Research and Development (R&D) with the 4D model, including Define, Design, Develop, and Disseminate. The instrument used was a set of questionnaires on validation, user practicability, and student responses to the e-module, distributed to 25 students. The e-module was rated as valid by media experts (82%) and material experts (84%) and very practical according to teacher assessment (89.09%) and practical according to student assessment (84.07%). The results showed that students' scores after using the e-module were higher than the scores before using the e-module, indicating the effectiveness of the e-module in improving students’ critical thinking skills and understanding of the learning. The findings emphasize the importance of technology integration in vocational high schools to prepare students for future jobs and encourage innovation in 21st century learning methodologies.